Antioxidant Activity of Extracts Obtained by Applying Various Solvents to the Local Brown Sorghum (Sorghum bicolor) Bran - Dewi, Juwita Ratna; Estiasih, Teti; Murtini, Erni Sofia (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
A completely randomized design experiment was conducted to determine the antioxidant activity of bran extracts obtained by applying various solvents to the local brown sorghum grain. Four types of technical grade of solvents were employed, namely aquadest, ethanol 96%, methanol 98% and acetone 98%. Each bran extract was obtained by shaking for 8 hrs in a single solvent, respectively. The extract was vacuum dried prior to use. The antioxidant activity of the extract was assessed by determining its ability for free radicals (DPPH) scavenging and for the ability for oxidation inhibition of a particular fatty acid with ferric thiocyanate.The results indicated that the levels of phenols, tannin and anthocyanin, varied with the solvent and the methanol extract contained the highest level of total phenols (55.7%). The highest radical scavenging activity was found at a concentration of 400 ppm. The methanol extract (400 ppm) showed the highest EC50 value (81,5 %), which was slightly lower than that of BHT. The order of oxidative inhibition, from the highest one, was the extracts of methanol > ethanol > acetone > aquadest. The value of the methanol extract was almost comparable the one of BHT. Both the scavenging activity and oxidative inhibition were correlated positively with the levels of tannin and other phenols, but negatively correlated with the anthocyanin content.Keywords: brown sorghum, bran extracts, antioxidant activity